Anti-Government Movements and the Revitalization Process:: An Examination of Anthony F.C. Wallace's Theory of Revitalization As Applied to Domestic Terrorist and Extremist Groups - Whitsel, Bradley (Journal of Conflict Studies, 2005)
ABSTRACT This article employs a case study approach to examine the usefulness of Anthony F.C. Wallace's classic theory of group revitalization as it relates to terrorist and extremist movements. Wallace's theory, while well-known in anthropological circles, has only rarely been applied to the study of contemporary anti-statist groups. This oversight is unfortunate since the theory helps to account for the growth of these groups without relying on reductionist explanations. The central case of the West Virginia Mountaineer Militia, a radical militia group of the mid-1990s, is examined here in some detail to consider the precepts of revitalization theory. Other movements of a similar style are more briefly addressed.